Impact of Disinvestment on Financial Performance of Select PSUs Post Liberalization - Singh, Rakhi; Agrawal, Vijay (Indian Journal of Finance, 2019)
The objective of this paper was to assess and analyze 20 financial ratios pertaining to profitability, operating efficiency, leverage, and liquidity of selected PSUs that had undergone disinvestment. The approach of disinvestment was welcomed in 1990s as a wholesome solution for sustainability of PSUs. This paper analyzed the profitability, liquidity, and solvency ratios of disinvested 37 listed PSUs of Maharatna, Navratna, and Miniratna categories and belonging to both manufacturing and service sectors. PSUs were once referred to be temples of modern India, but many of them got derailed from the profit-making objective post liberalization and turned to be wealth drainers. The PSUs were suddenly exposed to global competition which they were not used to since operating under a protected environment. The reforms were initiated out of compulsion as most of the PSUs were reeling and became uncompetitive in an open economy. The level playing field and competition stained the financial performances of the PSUs. The paper discussed the profitability, liquidity, and solvency ratios over a period of 16 years and analyzed the performance of the PSUs by focusing on factors of their sustainability. Further, this paper explored the impact of disinvestment on financial feasibility of the PSUs over two phases each of eight years based on volume of disinvestment in order to correlate the performance of PSUs phase-wise for understanding the disinvestment process vis-Ã -vis their prospects of sustainability.